TRANSFORMASI PEMBELAJARAN MATEMATIKA MELALUI MEDIA VIDEO BERBASIS CAPCUT: STUDI EKSPERIMEN PADA SISWA SMA NEGERI 22 MALUKU TENGAH - Haris Kolengsusu (Jurnal Pendidikan dan Ekonomi (JUPEK), 2026)
Mathematics learning at SMA Negeri 22 Maluku Tengah is still predominantly teacher-centered, with limited use of instructional media, resulting in low student motivation and learning outcomes. In response to the demands of digital transformation in the Industrial Revolution 4.0 and Society 5.0 era, CapCut-based instructional videos offer an innovative approach to presenting mathematical concepts in a more engaging, interactive, and accessible manner. This study aimed to examine the effect of CapCut-based video media on students' mathematics learning outcomes. A quantitative approach with a quasi-experimental method and a Pretest–Posttest Control Group Design was employed. The population consisted of all eleventh-grade students at SMA Negeri 22 Maluku Tengah. Samples were selected using cluster random sampling, resulting in Class XI-A as the experimental group and Class XI-B as the control group. The research instrument was a validated multiple-choice mathematics achievement test. Data were analyzed using descriptive and inferential statistics, including the Independent Sample t-test, N-Gain analysis, and Cohen's d effect size. The findings revealed that students in the experimental group achieved significantly higher learning outcomes than those in the control group. The N-Gain score was categorized as high, accompanied by a strong effect size, indicating that CapCut-based video media effectively improved students' mathematics learning outcomes. Therefore, CapCut-based instructional videos can serve as an effective and innovative learning medium for mathematics instruction in secondary schools.